(untitled) (Journal of Ideas in Health, 2025)
Background: Artificial intelligence (AI) is increasingly recognized as a transformative tool in healthcare management. In Iraq, the potential of AI remains underexplored due to systemic, infrastructural, and professional challenges. This narrative review explores the challenges, problems, and potential solutions of using AI to manage and control Iraq’s health system, with a particular focus on universal health coverage (UHC). Methods: A comprehensive literature review was conducted using PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2015 and 2025, complemented by WHO and Iraqi Ministry of Health reports. Results: The findings highlight barriers including capacity building, availability and accessibility of data, professional preparedness, and legal frameworks. Recent innovations and policy initiatives demonstrate opportunities for integration of AI to strengthen health service delivery and monitoring. Conclusion: AI adoption in Iraq requires multi-level reforms involving workforce training, legal regulation, robust digital infrastructure, and alignment with UHC objectives. These measures can enhance equity, efficiency, and resilience in Iraq’s health system.